2004
DOI: 10.1038/labinvest.3700184
|View full text |Cite
|
Sign up to set email alerts
|

Mice depleted of CD8+ T and NK cells are resistant to injury caused by cecal ligation and puncture

Abstract: We previously showed that beta 2 microglobulin knockout mice depleted of NK cells by treatment with antiasialoGM1 (b2MKO/aAsGM1 mice) are resistant to sepsis caused by cecal ligation and puncture (CLP). b2MKO mice possess multiple immunological defects including depletion of CD8 þ T cells. This study was designed to determine the contribution of CD8 þ T and NK cell deficiency to the resistance of b2MKO/aAsGM1 mice to CLPinduced injury. b2MKO/aAsGM1 mice and CD8 knockout mice treated with anti-asialoGM1 (CD8KO/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 29 publications
(31 reference statements)
8
60
0
Order By: Relevance
“…In this study, however, depletion of NK cells by anti-asialo GM1 antibodies did not significantly modify the survival curves. In contrast, NK cells contribute to the overzealous production of inflammatory cytokines associated with mortality of septic shock (86,184). Most interestingly, in the latter study, the beneficial effect of the deletion of NK cells by either anti-asialo GM1 or anti-NK1.1 antibodies was only seen when mice were treated with antibiotics.…”
Section: Benefits Versus Disadvantages Of Nk Cell Activation During Bmentioning
confidence: 71%
“…In this study, however, depletion of NK cells by anti-asialo GM1 antibodies did not significantly modify the survival curves. In contrast, NK cells contribute to the overzealous production of inflammatory cytokines associated with mortality of septic shock (86,184). Most interestingly, in the latter study, the beneficial effect of the deletion of NK cells by either anti-asialo GM1 or anti-NK1.1 antibodies was only seen when mice were treated with antibiotics.…”
Section: Benefits Versus Disadvantages Of Nk Cell Activation During Bmentioning
confidence: 71%
“…Leukocytes were depleted using anti-CD45-coated magnetic beads. This procedure yields ~95% pure satellite cells, based on their functional activity [22]. Sirt1 knockdown effects were confirmed by western blot using Sirt1 antibody (Santa Cruz Biothecnology, Inc., CA)…”
Section: Isolation Of Myofibers and Satellite Cellsmentioning
confidence: 99%
“…To our knowledge, this is the first case-control association study using CXCL2 as a candidate gene for sepsis susceptibility, although its key role in promoting inflammatory stress has been extensively studied in different models of the disease, [7][8][9][10][11][12] and has been listed as a candidate gene for susceptibility to lung injury occurring within the setting of critical illnesses. 3 The common disease-common variant hypothesis 27 proposes that most of the genetic risk for complex diseases is owing to common variants of the loci involved.…”
Section: Discussionmentioning
confidence: 99%
“…In a septic model, Walley et al 7 found that increased expression of CXCL2 was associated with the severity of sepsis, and that antibody blocking of CXCL2 activity decreased mortality. 8,9 Congruent with these results, different studies have shown that the attenuation of CXCL2 activity, by attenuating its expression by means of glucocorticoids 6 or by siRNA gene silencing, 10 by using inhibitors of its receptor 11 or using a model of CD8 þ T/NK cell-deficient mice in which the expression of CXCL2 is decreased, 12 leads to a reduction in inflammatory response and injury.…”
Section: Introductionmentioning
confidence: 93%